Approximate search for Big Data with applications in information security - A survey - Petrović, Slobodan (The European Journal of Applied Economics, 2015)
This paper is a survey of approximate search techniques in very large data sets (so-called Big Data). After a short introduction, some techniques for speeding up approximate search in such data sets based on exploitation of inherent bit-parallelism in computers are described. It then reviews the applications in search related to information security problems (digital forensics, malware detection, intrusion detection) are reviewed. Finally, the need for constraints in approximate search regarding the number of so-called elementary edit operations and the run lengths of particular elementary edit operations is explained and the status of on-going research on efficient implementation of approximate search algorithms with various constraints is given.